(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Due to the availability of several secondary metabolites, plants and their derivatives have historically been relied upon as a primary source of therapeutics. Many different plant families have been found to have compounds with possible anticancer effects. The purpose of this research was to use the SRB assay to assess the cancer-fighting effects of an ethanolic extract of three plants from different families, namely Croton bonplandianum Baill., Heliotropium indicum L., and Quisqualis indica L., on four different human cancer cell lines: melanoma (MDA-MB-231), chronic lung disease (A-549) and prostate cancer (PC-3) and hepatoma (HepG2). These three plants were tested for their cytotoxic activity (SRB assay) against these cancer cell lines. Different test material concentrations (10 gram/milligram, 20 gram/milligram, 40 gram/milligram, and 80 gram/milligram) were used to determine the level of activity. At 80ug/ml, only H. indicum showed a promising impact against melanoma (MDA-MB-231) and lung cancer (A549) cell lines, whereas C. bonplandianum and Q. indica had no effect (A-549).